Patients-Reported Outcomes of Acute Side Effects During Head and Neck Cancer Radiotherapy: A Cross-Sectional Study at Andalas University Hospital Padang - Ismail, Fikri Wahyuda; Rafli, Rhandyka; Putriyuni, Anandia (http://dharmais.co.id/, 2024)
Background: Head and neck cancer is a malignancy originating from the upper aerodigestive tract. Head and neck cancer patients undergoing radiotherapy using brachytherapy, 2DRT, 3CDRT, and IMRT techniques. Patients undergoing radiotherapy will experience several acute side effects consisting of mucositis, dysphagia, xerostomia, and dermatitis. This is influenced by the technique and dose given. This study aims to grade and time the acute side effects of radiotherapy for head and neck cancer at the Andalas University Hospital Padang. Methods: A quantitative descriptive method with a cross-sectional approach is used. Secondary data with a total sample of 88 patients. This research uses medical record data and is analyzed using statistical analysis methods. Results: This study found that the most head and neck cancer patients who underwent radiotherapy were male 57 (64.8%) patients, nasopharyngeal subsite 41 (46.6%) patients with non-keratinizing nasopharyngeal carcinoma 32 (36.4%) patients. The most common radiotherapy technique for head and neck cancer was IMRT in 58 (65.9%) patients with a dose of 61-70 Gy in 78 (88.6%) patients and the most common stage was IV A in 51 (58%) patients. Patients did not undergo chemotherapy treatment in 51 (58%) and surgery in 69 (78.4%). Body mass index (BMI) before radiotherapy was normal in 74 (84.1%) patients and after radiotherapy became underweight in 57 (64.8%) patients resulting in weight loss 1 kg in 83 (94.3%) patients. The highest grade of radiotherapy side effects was grade 1 which consisted of mucositis 84 (95.5%), dysphagia 83 (94.3%), xerostomia 78 (88.6%), and dermatitis 78 (88.6%) patients. The most frequent timing of mucositis side effects occurred in the 3rd week in 40 (45%) patients, dysphagia in the 3rd week in 41 (47%) patients, xerostomia in the 3rd week in 33 (38%) patients, and dermatitis at week 6 in 24 (27%) patients. Conclusions: Patients with head and neck cancer who undergo radiotherapy from week 1 to week 7 will experience side effects, including mucositis, dysphagia, xerostomia, and dermatitis. The average side effect appears in the 3rd week with grade 1.